Fracture development in shale and its relationship to gas accumulation - Ding, Wenlong; Li, Chao; Li, Chunyan; Xu, Changchun; Jiu, Kai; Zeng, Weite; Wu, Liming (Di xue qian yuan., 2012)
Shale with high quartz, feldspar and carbonate, will have low Poisson＇s ratio, high Young＇s modulus and high brittleness. As a result, the shale is conducive to produce natural and induced fractures under external forces. In general, there is a good correlation between fracture development in shale and the volume of brittle minerals present. Shale with high TOC or abnormally high pressure has well-developed fractures. Shale fracture development also shows a positive correlation with total gas accumulation and free gas volume, i.e., the better shale fractures are developed, the greater the gas accumulation and therefore the higher the gas production. Fractures provide migration conduits and accumulation spaces for natural gas and formation water, which are favorable for the volumetric increase of free natural gas. Wider fractures in shale result in gas loss. In North America, there is a high success ratio of shale gas exploration and high gas production from high-angle fracture zones in shale. Good natural gas shows or low yield producers in the Lower Paleozoic marine organic matter-rich rocks in the Sichuan Basin are closely related to the degree of fracture development in brittle shales.